Metode Penilaian Kinerja yang Efektif di ASEAN : Systematic Literature Review - Itaul Masarroh; Mochammad Isa Anshori (Ebisnis Manajemen, 2024)
Performance management is a systematic process used to improve organizational productivity by aligning individual, team and organizational goals. Effective HR management policies are key in helping companies recruit, develop, motivate and retain quality employees. This research uses the Systematic Literature Review (SLR) method as an approach to examine the issues raised, namely employee performance appraisal in a company. The results of the search and evaluation process in this systematic literature review resulted in 19 research journals relevant to the subject being studied. The results show that effective methods for global performance appraisal, such as 360-degree feedback, Management by Objectives (MBO), and performance appraisal feedback, are proven to improve performance quality by providing constructive feedback, ensuring the linkage of individual and organizational goals, and increasing employee motivation.